Bilateral simultaneous symmetrical intertrochanteric fracture - Agarwalla, Anish; Agarwal, Saumya; Mohindra, Mukul (Indian Journal of Case Reports, 2019)
A simultaneous bilateral intertrochanteric femur fracture is an extremely rare injury and there is paucity in the literature reportingthe best outcome with a bilateral surgery or a staged fixation. Here, we report the case of a 55-year-old male who sustained bilateralintertrochanteric femur fracture and operated in a staged manner with Dynamic Hip screw (DHS). After 6 months of surgery, thepatient was allowed to full weight bear and return to his routine office work.